2013
DOI: 10.1167/iovs.13-12901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Congenital Optic Disc Pits and Optic Disc Colobomas by Swept-Source Optical Coherence Tomography

Abstract: Swept-source OCT is able to detect different kinds of abnormalities including shape of cavities, defect of lamina cribrosa, or distance to SAS in the excavated optic discs anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 37 publications
(36 reference statements)
0
73
1
8
Order By: Relevance
“…The authors reported a defect in the lamina cribrosa at the site of the pit with herniation of nerve tissue into the pit. However, there was no description of the absence of the Space of Martegini, the attachment of vitreous fibres to the optic nerve head nor the presence of fibrouslooking tissue attached to the optic pit, as in our case [11].…”
Section: Discussioncontrasting
confidence: 62%
“…The authors reported a defect in the lamina cribrosa at the site of the pit with herniation of nerve tissue into the pit. However, there was no description of the absence of the Space of Martegini, the attachment of vitreous fibres to the optic nerve head nor the presence of fibrouslooking tissue attached to the optic pit, as in our case [11].…”
Section: Discussioncontrasting
confidence: 62%
“…Imaging should be used in such doubtful cases for ascertaining correct diagnosis. SSOCT has the ability to provide high-resolution images at deeper tissue levels and is a good tool for imaging ODC with pit 2. A large SSOCT imaging series on congenital optic disc anomalies has shown optic disc pits to vary in shape.…”
Section: Descriptionmentioning
confidence: 99%
“…A large SSOCT imaging series on congenital optic disc anomalies has shown optic disc pits to vary in shape. They can be triangular or slit-like, whereas dehiscence of the lamina cribrosa is common 2. The pit may contain vitreous fibres and herniated retinal tissue and has been seen to be very close to the subarachnoid space in some cases 2.…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations